Occlusal Vertical Dimension Analyzed By Digital Photography Using Graphic Design Softwares - Rani Purba; Ulfa Yasmin; Arya Prasetya Beumaputra; Puput Rizkika (Fakultas Kedokteran Universitas Sriwijaya, 2020)
The measurements of occlusal vertical dimension (OVD) is very important in the process of making denture. One method of them is indirectly with digital photography analysis using graphic design softwares. Some softwares used in digital photo analysis are cheap and easy for generalized use. There are several other softwares often used by graphics professionals that its application is a little more difficult. This study aimed to compare in the measurement results of occlusal vertical dimension analyzed by digital photography using graphic design softwares, and it was expected that their results approached the direct method. This study was an observational analytic study with a cross-sectional approach. The total sample in this study was amounted to 30 pre-clinical and clinical dentistry study programs at Universitas Sriwijaya. The measurements of occlusal vertical dimension were measured from subnational to menton in an occlusion state using the direct method (Willis) (control) and digital photography analysis of both softwares (Adobe Photoshop and Coreldraw). Data were tested using one-way ANOVA test. One-way ANOVA test results showed differences in the occlusal vertical dimension between the direct method and digital photography analysis of both softwares were not significant (P> 0.5). There was no difference in the results of the occlusal vertical dimension between the groups.